A bioprocess engineering approach for the production of hydrocarbons and fatty acids from green microalga under high cobalt concentration as the feedstock of high-grade biofuels - Alok Patel; Chloe Rantzos; Eleni Krikigianni; Ulrika Rova; Paul Christakopoulos; Leonidas Matsakas (Biotechnology for Biofuels and Bioproducts)
Abstract Botryococcus braunii, a colonial green microalga which is well-known for its capacity to synthesize hydrocarbons, has significant promise as a long-term source of feedstock for the generation of biofuels. However, cultivating and scaling up B. braunii using conventional aqua-suspended cultivation systems remains a challenge. In this study, we optimized medium components and light intensity to enhance lipid and hydrocarbon production in a multi-cultivator airlift photobioreactor. BBM 3N medium with 200 μmol/m2/s light intensity and a 16 h light–8 h dark regimen yielded the highest biomass productivity (110.00 ± 2.88 mg/L/day), as well as the highest lipid and hydrocarbon content. Cultivation in a flat-panel bioreactor resulted in significantly higher biomass productivity (129.11 ± 2.74 mg/L/day), lipid productivity (32.21 ± 1.31 mg/L/day), and hydrocarbon productivity (28.98 ± 2.08 mg/L/day) compared to cultivation in Erlenmeyer flasks and open 20-L raceway pond. It also exhibited 20.15 ± 1.03% of protein content including elevated levels of chlorophyll a, chlorophyll b, and carotenoids. This work is noteworthy since it is the first to describe fatty acid and hydrocarbon profiles of B. braunii during cobalt treatment. The study demonstrated that high cobalt concentrations (up to 5 mg/L of cobalt nitrate) during Botryococcus culture affected hydrocarbon synthesis, resulting in high amounts of n-alkadienes and trienes as well as lipids with elevated monounsaturated fatty acids concentration. Furthermore, pyrolysis experiments on microalgal green biomass and de-oiled biomass revealed the lipid and hydrocarbon compounds generated by the thermal degradation of B. braunii that facilitate extra economical value to this system.